(untitled) (Gremium, 2019)
Terra di Lavoro, an historical region north of Naples. Their urban centers, with historically, artistically and archaeologically of interest, suffered extensive damage in the Second World War (IIWW). When allied landing at Salerno, the continuous bombing produced heavy losses to the architectural heritage with destruction both in historical centers and in major monuments. The aim of this papers is present some experience on reconstruction applied in Terra di Lavoro. This paper was developed through the use of historical analysis. Institutional effort was analyzed in each case described. The outcomes of the economic and social policy conditioning had considerable importance as well as psychological and symbolic order. In conclusion, through the architectural heritage reconstruction, it begins a process strongly characterized by instances outside the scope of the protection and restoration, that pressed on economic and social revival of the nation through a rapid revival of tourism, from the restored face of the main monuments.